Pendampingan Holistik Menyusui terhadap Produksi ASI Melalui Kadar Hormon Prolaktin pada Ibu Nifas Normal - Yolanda Indri Octaviani; Suharyo Hadisaputro; Aris Santjaka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to prove the effect of holistic breastfeeding assistance, which includes psychoeducation, oxytocin massage, and mural Al-Qur'an, which can increase milk production through prolactin hormone levels. The research method used in this study was a quick experiment with a pretest and a posttest with a control group design. The results showed that after being given holistic breastfeeding assistance for seven days, there were differences in prolactin hormone levels in the intervention group and the control group. The increase in prolactin hormone levels in the intervention group between before and after treatment occurred by 67.56 (27%). In conclusion, there is a significant relationship between holistic breastfeeding assistance given for 30 minutes every day for seven days to increase milk production and levels of the hormone prolactin. Keywords: Milk Production, Prolactin, Holistic Breastfeeding Assistance, Murrotal Al-Qur'an, Oxytocin Massage